1999
DOI: 10.1017/s0033291798008046
|View full text |Cite
|
Sign up to set email alerts
|

Apathy and depressed mood in acquired brain damage: relationship to lesion localization and psychophysiological reactivity

Abstract: Apathy is common, its severity depending on diagnosis and localization of lesion. Apathy and depression in brain damaged patients share common features, but may be differentiated. The significant relationship between apathy and heart rate may provide a psychophysiological correlation of the disengagement, lack of interest and absence of emotional responsivity typically seen in apathy. The results have implications for the theoretical understanding of apathy and related negative symptoms, and for rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
127
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(147 citation statements)
references
References 49 publications
14
127
2
4
Order By: Relevance
“…Finally, a functional study has reported a relationship between apathy and hypoperfusion of both frontal lobes after stroke [29]. Interestingly, Andersson et al [5] reported that Apathy Evaluation Scale (AES) mean score was higher in right damaged patients, but that only in left damaged patients it was correlated to the severity of depressive symptoms.…”
Section: Psychiatric Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a functional study has reported a relationship between apathy and hypoperfusion of both frontal lobes after stroke [29]. Interestingly, Andersson et al [5] reported that Apathy Evaluation Scale (AES) mean score was higher in right damaged patients, but that only in left damaged patients it was correlated to the severity of depressive symptoms.…”
Section: Psychiatric Historymentioning
confidence: 99%
“…The association between older age and apathy has been generally interpreted as the expression of the physiological involution of dopaminergic circuitry in normal aging [5,26], or as a "consequence of response to uncontrollable stress and problems associated with ascending age" [5].…”
Section: Psychiatric Historymentioning
confidence: 99%
“…Kant et al (69) found that it occurred (mixed with depression) in 60% of their sample. Andersson et al (70) found that almost half of their individuals with TBI had significant degrees of apathy. Deficits in motivated behavior can occur in association with injury to the circuitry of "reward" (68,71).…”
Section: Changes In Personalitymentioning
confidence: 99%
“…however, apathy can occur without depression in Ad and when depression and apathy co-occur in Ad patients, it has been shown that they are clinically and anatomically independent [20][21][22] . Indeed, in order to discriminate apathy from depression, several scales have been designed to quantify apathy, which wisely exclude symptoms such as sadness and negative thoughts, typically observed in depressive syndromes 15,[23][24][25][26][27] .…”
mentioning
confidence: 99%